Immunization of a novel bivalent outer membrane protein simultaneously resisting Aeromonas hydrophila, Edwardsiella anguillarum and Vibrio vulnificus infection in European eels (Angullia angullia). Issue 97 (February 2020) - Guo, Songlin; He, Le; Wu, Liqun; Xiao, Yiqun; Zhai, Shaowei; Yan, Qinpi
Abstract: In cultivated European eels, Aeromonas hydrophila, Edwardsiella anguillarum and Vibrio vulnificus are three important bacterial pathogens. In this study, European eels ( Anguilla anguilla ) were immunized by the bivalent expression products of the outer membrane protein (Omp) gene from A. hydrophila (OmpⅡ) and E. anguillarum (OmpA), and the effects of the bivalent protein (rOmpⅡ-A) on the immune function of the European eel were detected. Three hundred eels were divided average into three groups of PBS, adjuvant and rOmp. Eels of three goups were injected intraperitoneal with 0.2 mL of PBS (0.01 mol/L, pH7.4), PBS + F (PBS mixed equal volume of freund's uncomplete adjuvant) or rOmpⅡ-A (1 mg mL −1 rOmpⅡ-A mixed equal volume of freund's uncomplete adjuvant). Four immune-related genes expression, proliferation of whole blood cells, serum and skin mucus antibody titer, superoxide dismutase (SOD) activity and the relative percent of survival (RPS) were studied at different days (or hours) post the immunization. The results showed that the igm, lysC, mhc2 and sod gene in the liver, spleen, kidney and intestine tract were significant increased in the Omp group; On the 28 day post the immunization (dpi), blood cell proliferation was increased in the Omp group, and on the 14, 21, 28 and 42 dpi, antibody titers in serum and mucus of the Omp group were significantly higher than that of the PBS and adjuvant group, regardless of coating with bacteria or Omp antigen. The SOD activity of Omp group increased significantly in liver, kidney, skin mucus and serum from 14 to 42 dpi, especially in serum. Eels chanllenged by A. hydrophila, E. anguillarum and V. vulnificus in the bivalent Omp group showed the RPS were 83.33%, 55.56% and 44.44%, respectively. The results of this study showed that immunization of the bivalent Omp could effectively improve the immune function of European eels, and produced effectively protection to A. hydrophila and E. anguillarum infection. Simultaneously, the bivalent Omp also produced distinct cross-protection to the eels challenged by V. vulnificus . Highlights: A novel bivalent rOmp from A. hydrophila and E. anguillarum was expressed. European eels immunized with the rOmp induces higher protective effects. Protective effect was mainly related to the presence of specific antibodies. Protective effect was partly related to the immune-related gene and SOD activity.